New strategies for the evaluation of Vanadium Flow Batteries: testing prototypes. (September 2022) - Trovò, Andrea; Poli, Nicola; Guarnieri, Massimo
Abstract : This paper presents a review of methods for assessing the performance of all-Vanadium Flow Batteries (VFBs), derived from the experience deduced on laboratory kW-class VFB facilities. The main factors affecting the performance of VFBs, namely thermal, hydraulic, electric, and energetic, are identified and the main strategies for assessing them are discussed. An analysis of the different loss terms involved in large VFBs is presented. Thereafter criteria and methods for the unambiguous evaluation and comparison of the performance of these devices are proposed. Capacity fades are also considered, their causes are analyzed and measures to counteract them are presented. The state of art of flow batteries international standard and regulation is also reported. The final aim of the paper is contributing to the development of metrics for the industrialization of VFBs. Highlights: An overview of methods for evaluating industrial Vanadium Flow Batteries is given. Thermal, hydraulic, electric, and efficiency tests are described. The differences between testing flow batteries single cells and stacks are explained. Regulation and standards are also presented. These topics play a role in the industrializations and marketing of flow batteries.